THE RELATIONSHIP BETWEEN BURNOUT AND JOB SATISFACTION: A CASE STUDY OF IRAQI EFL TEACHERS IN SPECIAL EDUCATION - AL-Zurfi, Ali; Sameer Bilal; Talib Ghaleb (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study investigated the relationship between burnout and job satisfaction among Iraqi EFL teachers working with students with special needs. Method: Using the Maslach Burnout Inventory (MBI) and a Job Satisfaction Scale, data were collected from 41 teachers in public schools, private schools, and private institutions. Results: The results reveal a strong negative correlation between emotional exhaustion and job satisfaction, a moderate negative correlation between depersonalization and job satisfaction, and a strong positive correlation between personal accomplishment and job satisfaction. Novelty: The findings suggest that improving teachers' sense of competence and achievement can enhance job satisfaction and reduce burnout. The study highlights the need for targeted interventions to support the well-being of special education teachers in Iraq.